Primera cita del parasitoide Tripobius semiluteus Boucek (Hymenoptera: Eulophidae) en España - Beltra, A.=700 1 Soto, A.
(Es, En)
Ilus; 18 ref.
Keywords: HYMENOPTERA; INSECTA; PARASITOIDES; CONTROL BIOLOGICO; HELIOTHRIPS; PLANTAS ORNAMENTALES; ESPAÑA; THRIPOBIUS SEMILUTEUS; BOLETIN DE SANIDAD VEGETAL: PLAGAS